2021
DOI: 10.21203/rs.3.rs-138252/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chlorpheniramine maleate nasal spray in COVID-19 patients: Case Series

Abstract: The pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) posted a devastating global health crisis for almost a year already. Very little is known about this virus that scientists, physicians and the medical community struggled to find treatments of this novel virus. The vaccine that can potentially combat this virus is still an unknown reality hence, the repurposing of existing medical treatments such as chlorpheniramine maleate (CPM) could be a possible treatment and is being widely utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Mounting evidence suggests that CPM has both antiviral and anti-in ammatory actions that could be bene cial in treating COVID-19 [11,[18][19][20]29]. Furthermore, molecular modeling and preliminary clinical data analyzed the antiviral activity of CPM, comparing the chemical structure of different over-the-counter drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence suggests that CPM has both antiviral and anti-in ammatory actions that could be bene cial in treating COVID-19 [11,[18][19][20]29]. Furthermore, molecular modeling and preliminary clinical data analyzed the antiviral activity of CPM, comparing the chemical structure of different over-the-counter drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Mostafa et al, 2020; Westover et al, 2020; Xu et al, 2018). Furthermore, early clinical studies have indicated CPM’s effectiveness in treating COVID-19 (Black, 2022; Morán Blanco et al, 2021; Sanchez-Gonzalez et al, 2022; Torres et al, 2021). Our research team has also reported on the safety and efficacy of intranasally administered CPM for the treatment of COVID-19 and allergic rhinitis (Sanchez-Gonzalez et al, 2021; Sanchez-Gonzalez et al, 2022).…”
Section: Introductionmentioning
confidence: 99%